Metabotropic Glutamate Receptor 2/3 (mGluR2/3) Activation Suppresses TRPV1 Sensitization in Mouse, But Not Human, Sensory Neurons - Sheahan, Tayler D. (eNeuro, 2018)
The use of human tissue to validate putative analgesic targets identified in rodents is a promising strategy for improving the historically poor translational record of preclinical pain research. We recently demonstrated that in mouse and human sensory neurons, agonists for metabotropic glutamate receptors 2 and 3 (mGluR2/3) reduce membrane hyperexcitability produced by the inflammatory mediator prostaglandin E(2) (PGE(2)). Previous rodent studies indicate that mGluR2/3 can also reduce peripheral sensitization by suppressing inflammation-induced sensitization of TRPV1. Whether this observation similarly translates to human sensory neurons has not yet been tested. We found that activation of mGluR2/3 with the agonist APDC suppressed PGE(2)-induced sensitization of TRPV1 in mouse, but not human, sensory neurons. We also evaluated sensory neuron expression of the gene transcripts for mGluR2 (Grm2), mGluR3 (Grm3), and TRPV1 (Trpv1). The majority of Trpv1 (+) mouse and human sensory neurons expressed Grm2 and/or Grm3, and in both mice and humans, Grm2 was expressed in a greater percentage of sensory neurons than Grm3. Although we demonstrated a functional difference in the modulation of TRPV1 sensitization by mGluR2/3 activation between mouse and human, there were no species differences in the gene transcript colocalization of mGluR2 or mGluR3 with TRPV1 that might explain this functional difference. Taken together with our previous work, these results suggest that mGluR2/3 activation suppresses only some aspects of human sensory neuron sensitization caused by PGE(2). These differences have implications for potential healthy human voluntary studies or clinical trials evaluating the analgesic efficacy of mGluR2/3 agonists or positive allosteric modulators.